2018
DOI: 10.1038/s41598-018-35694-9
|View full text |Cite
|
Sign up to set email alerts
|

Development a stacking pad design for enhancing the sensitivity of lateral flow immunoassay

Abstract: Lateral flow immunoassays (LFIAs) have wide application in point-of-care testing, particularly in resource-poor settings. To achieve signal amplification in a gold nanoparticle-based lateral flow assay without an additional procedure or the need for complex fabrication, a new and simple method was developed for using a “stacking pad” configuration that adds an additional membrane between the conjugation pad and test pad to the conventional AuNP-based LFIA format. This design helps to accumulate the antibody an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 52 publications
2
60
1
1
Order By: Relevance
“…For example, Anfossi et al [ 45 ] reported that the LFIA for ochratoxin A detection using a silver system was 10-fold more sensitive than the conventional gold-based LFIA that otherwise used the same immuno-reagents. However, the silver reagent was relatively unstable and highly light sensitive [ 16 ]. Recently, Tsai et al (2018) [ 16 ] reported the use of a stacking pad (additional membrane between the conjugation pad and test pad) for enhancing the sensitivity of the LFIA for detection of protein A and C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Anfossi et al [ 45 ] reported that the LFIA for ochratoxin A detection using a silver system was 10-fold more sensitive than the conventional gold-based LFIA that otherwise used the same immuno-reagents. However, the silver reagent was relatively unstable and highly light sensitive [ 16 ]. Recently, Tsai et al (2018) [ 16 ] reported the use of a stacking pad (additional membrane between the conjugation pad and test pad) for enhancing the sensitivity of the LFIA for detection of protein A and C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, the silver reagent was relatively unstable and highly light sensitive [ 16 ]. Recently, Tsai et al (2018) [ 16 ] reported the use of a stacking pad (additional membrane between the conjugation pad and test pad) for enhancing the sensitivity of the LFIA for detection of protein A and C-reactive protein. The stacking pad helped to extend the binding interaction of antigen and antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we introduced a multi-target lateral flow immunoassay strip (msLFIA), which added an additional membrane between the conjugation pad and the test pad to the conventional AuNP-based LFIA format to enhance the detection sensitivity 39 , for measuring the protein levels of alpha-defensin and CRP in synovial fluid samples from patients undergoing revision arthroplasty for septic or aseptic failure. In the previous study 39 , synovial fluid sample was pre-treated with a 1:100 dilution in PBS buffer because the pure synovial fluid is viscous and difficult to flow through the strip completely; however, in this study, we performed a quick preincubation of mixing the pure synovial fluid sample with the AuNPs-labeled antibodies, so the protein levels in synovial fluid are specific for analyte without dilution. We aimed to develop a multiplex LFIA for rapid and high performance for PJI diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst these sophisticated platforms achieve improved performance, they do involve either high-cost biochemical reagents such as enzymes 15,16 , external equipment such as electrophoresis apparatus 17,21 , complex fabrication 14 or multiple-step operation 4,10 . Simplified and more cost-effective methods to improve the sensitivity of LFA are needed to be truly implemented for the rapid in-situ detection 25 .…”
mentioning
confidence: 99%